2009
DOI: 10.1002/jor.20769
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of murine intrasynovial tendon adhesions following injury: MMP and neotendon gene expression

Abstract: Tendon injury frequently results in the formation of adhesions that reduce joint range of motion. To study the cellular, molecular, and biomechanical events involved in intrasynovial tendon healing and adhesion formation, we developed a murine flexor tendon healing model in which the flexor digitorum longus (FDL) tendon of C57BL/6 mice was transected and repaired using suture. This model was used to test the hypothesis that murine flexor tendons heal with differential expression of matrix metalloproteases (MMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
179
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(185 citation statements)
references
References 31 publications
6
179
0
Order By: Relevance
“…Mast cells have also been implicated in the process of scarring (fibrosis), 29 a well-known negative sequela of tendon repair. 30 Sodium cromolyn is available as a mast cell stabilizer for local or systemic application for conditions including asthma, dermatitis, mastocytosis, and rheumatoid arthritis. Although SC treatment influenced the expression of genes related to extracellular matrix metabolism in the current study, the exact mechanisms of action remain to be elucidated.…”
Section: Mast Cells In Patellar Tendon Injurymentioning
confidence: 99%
“…Mast cells have also been implicated in the process of scarring (fibrosis), 29 a well-known negative sequela of tendon repair. 30 Sodium cromolyn is available as a mast cell stabilizer for local or systemic application for conditions including asthma, dermatitis, mastocytosis, and rheumatoid arthritis. Although SC treatment influenced the expression of genes related to extracellular matrix metabolism in the current study, the exact mechanisms of action remain to be elucidated.…”
Section: Mast Cells In Patellar Tendon Injurymentioning
confidence: 99%
“…Further studies examined the ultrastructural, compositional and mechanical characteristics of the Achilles tendon in rodents deficient in GDF-5, and found the maximum load to failure decreased possibly due to significantly less collagen, an increase in irregularly shaped Col I fibrils and compromised material behaviour (decrease in strength and stiffness) [140][141][142]. Therefore unsurprisingly, GDF-5 has been shown to increase mechanical strength in these rodent models [143][144][145][146]. These studies are further supported at a cellular and gene level by studies showing an improved collagen organisation with GDF-5 treatment [147,148], as well as an increased expression of genes and synthesis of the components of tendon ECM, in particular, Col I, Ten C and MMP-3 [149].…”
Section: Functionmentioning
confidence: 99%
“…αSMA immunostaining, × 400. of these fibrils into bundles of collagen becomes easily discernible by the 21st postoperative day. Other researchers [30] confirmed that this strictly linear uniaxial organization of collagen fibrils and the linear alignment of the spindle-shaped tenocytes between them have to be re-established in tendon during healing-remodeling processes. Accordingly, in the present study, the best healing results were found in subgroup IVb.…”
Section: Discussionmentioning
confidence: 83%